2020
DOI: 10.1002/ece3.6340
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐scale structure among mesophotic populations of the great star coral Montastraea cavernosa revealed by SNP genotyping

Abstract: Mesophotic reefs (30‐150 m) have been proposed as potential refugia that facilitate the recovery of degraded shallow reefs following acute disturbances such as coral bleaching and disease. However, because of the technical difficulty of collecting samples, the connectivity of adjacent mesophotic reefs is relatively unknown compared with shallower counterparts. We used genotyping by sequencing to assess fine‐scale genetic structure of Montastraea cavernosa at two sites at Pulley Ridge, a mesophotic coral reef e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 89 publications
1
8
0
Order By: Relevance
“…It would seem that coral planulae may be less successful in migrating from deeper habitats to shallow ones and establishing there, than the other way around (Prada & Hellberg, 2021; Rippe et al, 2021; Serrano et al, 2014; Shlesinger & Loya, 2021). Indeed, the current findings are consistent with several studies suggesting that population connectivity along depth may be relevant only for some depth‐generalist species but not for all, or not in all biogeographic regions (Bongaerts et al, 2017; Drury et al, 2020; Liberman et al, 2018; Rippe et al, 2021; Scucchia et al, 2021; Serrano et al, 2014; Shlesinger et al, 2018; Shlesinger & Loya, 2021). Taken together with our findings of reduced reproductive activity at mesophotic depth, it seems less likely that migrating into the deeper MCEs can provide corals with a long‐term viable refuge that will enable them to successfully replenish and sustain shallow‐water populations.…”
Section: Discussionsupporting
confidence: 91%
“…It would seem that coral planulae may be less successful in migrating from deeper habitats to shallow ones and establishing there, than the other way around (Prada & Hellberg, 2021; Rippe et al, 2021; Serrano et al, 2014; Shlesinger & Loya, 2021). Indeed, the current findings are consistent with several studies suggesting that population connectivity along depth may be relevant only for some depth‐generalist species but not for all, or not in all biogeographic regions (Bongaerts et al, 2017; Drury et al, 2020; Liberman et al, 2018; Rippe et al, 2021; Scucchia et al, 2021; Serrano et al, 2014; Shlesinger et al, 2018; Shlesinger & Loya, 2021). Taken together with our findings of reduced reproductive activity at mesophotic depth, it seems less likely that migrating into the deeper MCEs can provide corals with a long‐term viable refuge that will enable them to successfully replenish and sustain shallow‐water populations.…”
Section: Discussionsupporting
confidence: 91%
“…Whether our findings generally hold for corals as well as for other marine organisms, awaits similar assessments of broadcast-spawning species to be carried out. Yet, despite the natural variability between species and sites, genetic segregation of both the coral host and its symbionts across depth was found to date in both brooding and spawning corals 10,[42][43][44][45][46][47][48][49][50]83,84 . Regardless, our results demonstrate that although not fully hindered, corals' early life-history stages may have differential success and fitness in different conditions, depending on their natal habitats.…”
Section: Resultsmentioning
confidence: 99%
“…At the community level, coral reefs have long been recognized as displaying a distinct depth zonation, dominated by different species [91][92][93][94][95][96][97] . At the population level, recent studies have also found evidence of ecological adaptive divergence and genetic segregation across depth in several species and localities 10,[42][43][44][45][46][47][48][49][50]83,84 . Here, we have shown that local adaptations and parental effects may considerably influence brooding coral abundance across depth through selective larval settlement and phenotype-environment mismatches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Applying molecular techniques to the depth-stratified collection of corals can characterize potential ecological differences between shallow and mesophotic populations of depth-generalist coral species and begin to evaluate the refugia potential of mesophotic populations (Bongaerts et al, 2015;Studivan and Voss, 2018b;Eckert et al, 2019;Drury et al, 2020;Eckert et al, 2020;Sturm et al, 2021). Restriction-site associated DNA sequencing (RADseq) methods have become an increasingly popular tool in the field of coral population genetics, as they allow for relatively inexpensive but high-resolution genotyping (on the order of thousands of single nucleotide polymorphisms, SNPs; Puritz et al, 2014).…”
Section: Introductionmentioning
confidence: 99%